Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/ene.12107
|View full text |Cite
|
Sign up to set email alerts
|

A short and validated multiple sclerosis‐specific health‐related quality of life measurement for routine medical practice

Abstract: Compared with existing alternatives, our 10-item three-dimensional Hr-QoL measurement tool is adapted to RMP, and constitutes an adequate compromise between precision and ease of use in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Disease-specific tools developed for measuring QoL/ADL in MS and ALS patients [69,70] might also be applicable to late-onset Pompe patients.…”
Section: Methodsmentioning
confidence: 99%
“…Disease-specific tools developed for measuring QoL/ADL in MS and ALS patients [69,70] might also be applicable to late-onset Pompe patients.…”
Section: Methodsmentioning
confidence: 99%
“…At baseline, we measured alexithymia (TAS-20) scale [31], Beck Depression inventory [31], Anxiety STA-I [31], emotional distress (POMS) [31], assertiveness and selfesteem scales [31], [32]. Neuropathic pain scale (DN4), severity fatigue scale (FSS), sleeping disorder scales (Epworth), EDSS [33] and self-filled validated short TLS-QoL 10 [27] and DC10 [28] scales were used at every visit. All the scales were administered in conformity with CBT.…”
Section: Measurementsmentioning
confidence: 99%
“…The essential concern of QoL in this pathology motivated us to provide further investigation on the beneficial effect of CBT. Aware of these methodological problems, we postponed the therapy trial, in concentrating first to the development of adapted measurement tools: a literature review [27], [28] showed that there was no scale of QoL or coping conducted in the same time specific to MS and adapted to routine practice. A first cross-sectional study of 331 patients [27] identified a short MS-specific optimized QoL scale of 10 items (TLS-QoL 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis is considered the prototypic neuro‐inflammatory disease. It is now recognized to have a significant genetic component, although no single gene mutations have been identified, so again this is likely to be a complex genetic influence on risk.…”
mentioning
confidence: 99%